Perancangan Sistem Deteksi Dini Pencegah Kebakaran Rumah Berbasis ESP8266 dan Blynk - tatik juwariyah (TRANSISTOR Elektro dan Informatika, 2018)
Home fire accidents that start from LPG leakage in the kitchen space often occur around us. One of the solutions to secure the kitchen from potential fires is to apply smart home technology. The purpose of this study was to design an fire prevention early detection system based on Arduino, gas sensor, fire sensor, ESP8266 and Blynk application-based notification system on smartphones. The system design consits of a series of hardware that work in accordance with the command software. The hardware circuit consists of the Arduino Mega2560 microcontroller, the MQ6 Gas sensor, the flame sensor and the ESP8266 board as an embedded chip that communicate WiFi-based. The ESP8266 module is used as a client from a WiFi router. The function of this module is to send and receive information data between the microcontroller and smartphone. The communication is supported by the Blynk Llibraries and the Blynk Application as a graphical user interface on an android smartphone. The results of the system design were first tested as a fire detection device. The response of the system to the presence of fire is changing the color of virtual LED in the Blynk application. Further testing of the fire detection system is in the form of data on variations in the distance of fire sensors and sources of fire on system response time. Another separate test is to detect the presence of LPG leakage. The response of the system to the presence of LPG leakage is in the form of changing Blynk's virtual LEVEL on smartphone. The changing of the virtual level represents the gas concentration value declared by the gas sensor voltage values. The results of the design of the smarthome are expected to be one of the references for IoT-based fire potensial prevention systems.Key words:Blynk, ESP8266, flame sensor , gas sensor , IoT, smart home